2022
DOI: 10.3389/fmars.2022.966304
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying baseline costs and cataloging potential optimization strategies for kelp aquaculture carbon dioxide removal

Abstract: To keep global surface warming below 1.5°C by 2100, the portfolio of cost-effective CDR technologies must expand. To evaluate the potential of macroalgae CDR, we developed a kelp aquaculture bio-techno-economic model in which large quantities of kelp would be farmed at an offshore site, transported to a deep water “sink site”, and then deposited below the sequestration horizon (1,000 m). We estimated the costs and associated emissions of nursery production, permitting, farm construction, ocean cultivation, bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 117 publications
1
17
0
Order By: Relevance
“…Recently Coleman et al (2022) provided the first detailed published estimates on the costs of a potential ocean afforestation via a bio-techno-economic model. They found that there would be a cost of $17,048 tCO 2 eq -1 , but by optimising parameters on ocean afforestation this could be reduced to $1,257 tCO 2 eq -1 .…”
Section: Economic Feasibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Recently Coleman et al (2022) provided the first detailed published estimates on the costs of a potential ocean afforestation via a bio-techno-economic model. They found that there would be a cost of $17,048 tCO 2 eq -1 , but by optimising parameters on ocean afforestation this could be reduced to $1,257 tCO 2 eq -1 .…”
Section: Economic Feasibilitymentioning
confidence: 99%
“…boat fuel emissions and construction of aquaculture infrastructure) of the operation of any ocean afforestation project should be subtracted from any potential carbon sequestration via ocean afforestation (Coleman et al, 2022). Coleman et al (2022) calculated that potential CO 2 sequestration was reduced from 638 tons to 244 tons of net emissions once operational emissions were subtracted and that did not include boat emissions to transport to the sink site [Figure 5 in Coleman et al (2022)]. This suggests operational emissions may be considerable for some types of ocean afforestation operations.…”
Section: Economic Feasibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…No set CO 2 emission cap. The carbon offset market price is predefined Ton Metric ton (1,000 kg) $ (or dollar) US Dollar (USD; unless otherwise noted) Coleman et al 2022, Daneshvar et al 2022. Concurrently, shellfish production has been suggested as a sustainable form of protein, due to their low associated GHG emissions (Ray & Fulweiler 2020, Gephart et al 2021, Naylor et al 2021, and oyster aquaculture has been estimated to have less than 0.5% of the GHG cost of other animal protein sources (Ray et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To address these challenges, multiple industries have been developing green technologies to reduce (e.g., green energy, electric vehicles) and remove CO 2 via storage or chemical weathering (de Lannoy et al 2018, Bach et al 2019, Kazemifar 2021, Galimova et al 2022, Raza et al 2022), effectively sequestering atmospheric CO 2 over long (geological) timescales. In addition, proposed ocean-based removals of emissions include bio fixation by algae and kelp (Chung et al 2013, Coleman et al 2022, Daneshvar et al 2022). Concurrently, shellfish production has been suggested as a sustainable form of protein, due to their low associated GHG emissions (Ray & Fulweiler 2020, Gephart et al 2021, Naylor et al 2021), and oyster aquaculture has been estimated to have less than 0.5% of the GHG cost of other animal protein sources (Ray et al 2019).…”
Section: Introductionmentioning
confidence: 99%